Pengembangan Media E-Comic Dengan Pendekatan CTL Berbasis Cerita Rakyat Bengkulu Selatan Dalam Meningkatkan Kecerdasan Naturalis Siswa Kelas IV - Rahmi Oktarina; Abdul Muktadir; Gumono (UNIB Press, 2026)
This study aimed to develop, assess the feasibility, examine user responses, and determine the effectiveness of an E-Comic learning medium designed using the Contextual Teaching and Learning (CTL) approach and based on South Bengkulu folktales to enhance the naturalist intelligence of Phase B students in Grade IV at SDN 4 Bengkulu Selatan. This research employed a Research and Development (R&D) design using the ADDIE model. Both quantitative and qualitative data were collected through interviews, needs analysis questionnaires, tests, expert validation sheets, and user response questionnaires. The findings indicate that the developed E-Comic is feasible for use as a learning medium in the Grade IV Indonesian Language subject. Validation results from material, design, and language experts met valid criteria. User responses were highly positive, as shown by the teacher questionnaire results categorized as very good, and student responses also falling into the very good category. The E-Comic was proven effective in improving students’ naturalist intelligence, as indicated by the implementation class achieving an N-Gain score of 0.635. This demonstrates a significant difference between pre-test and post-test scores in the class that used the E-Comic at SD Negeri 4 Bengkulu Selatan.